Cloud Computing and Sustainability: An Australian Public Sector Perspective - Chang, Vanessa; Issa, Theodora; Issa, Tomayess (International Society for Professional Innovation Management (ISPIM), 2011)
Businesses are compelled to shift their organizations’ strategies to focus on sustainable growth. The recent summits in Copenhagen and Cancun have alerted businesses of their corporate social and environmental responsibilities. This require a shift in mindset that it is no longer the economic and financial stability that will drive an organization’s success but the longevity and sustainability of any organizations are also heavily dependent on their social and environmental outlook. An organization may no longer be sustainable if their social and environmental approach is de-coupled from the organization’s strategies. A way forward might be through the application of ethical management integrated with a full understanding of the agile and innovative technological solutions. This paper provides findings from a survey of the Australian public sector organizations of the awareness of cloud computing technology and the attitudes toward this innovative business solution. Two hundred and forty responses were received from the public sector organizations in Australia. The findings reveal that cloud computing technology is an important trend, and it can be concluded that it is extremely important for business leaders in their entirety, not just the IT managers, to understand the great potential that cloud computing technology has to offer.